Climate Change, Public Health, Health Policy, and Nurses Training - Harris, Orlando O.; Bialous, Stella Aguinaga; Muench, Ulrike; Chapman, Susan; Dawson-Rose, Carol (American journal of public health (1971), 2022)
There are few educational programs in the United States that have a primary focus on preparing nurses to engage in all levels of public health, health policy, and climate change. The United Nations sustainability development goals (SDG) and the Future of Nursing 2020–2030: Charting a Path to Achieve Health Equity (2021) report underscored the importance of key stakeholders, including nurses, engaging in advocacy and policy to promote health equity. We discuss the role of nursing at the intersection of public health, policy, climate change, and the SDG. We also discuss the history and merger of the University of California San Francisco (UCSF) School of Nursing public health and health policy specialties, a significant innovation in our effort to promote health equity. We provide a brief overview of the redesigning of our curriculum that meets the needs of today’s learners by including content on climate change, data analytics, and racial, social, and environmental justice. Finally, we emphasize the need to train the next cadre of nurses interested in careers in public health and health policy for us to meet the challenges facing our communities. (Am J Public Health. 2022;112(S3):S321–S327. https://doi.org/10.2105/AJPH.2022.306826 )